Digital metasurface for selective information distribution in the spatial domain in the THz region - Paul A.; Nilotpal; Bhattacharyya S.; Dwivedi S. (My University, 2025)
This paper presents a new, to the best of our knowledge, technique to control the flow of electron packets employing a switchable digital metasurface in the terahertz region. The proposed structure can act as a device that converts an electromagnetic (EM) wave into electron packets that can be represented in the form of digital bit sequences at the output. The top layer of the structure controls the intensity of the electron packets while the bottom layer involves the spatial distribution of the information with the help of electrical switching. The electrical switching is achieved with the application of suitable biasing across a vanadium dioxide (VO2) patch. This approach to the distribution of information helps feed the circuitry of an electronic system, as per the requirement using electrical tuning, which is not possible in a conventional antenna system. © 2022 Optica Publishing Group